How does the removal of repetitive tasks affect motivation? -A study of motivation within shared service centers - Olsson,Johan; Raso,David (2019)
Purpose: The purpose of this study is to investigate how the removal of repetitive tasks would affect employees’ motivation. Theoretical framework: The theoretical framework of this thesis is built upon theory regarding motivation, feedback, boring tasks and commitment. Methodology: A qualitative empirical research approach consisting of a multi-case study. Empirical foundation: The empirical data consists of primary data. The data was collected through multiple interviews with managers and employees. Conclusions: The study suggests that the motivation of the employees working within an shared service center at accounts payable experience an increase in their intrinsic motivation when they feel committed to their work tasks and when they perform a variety of tasks. The study also suggests that the reason for an shared service center’s existence, the specialization of tasks, is in itself not motivating for the employees.
Keywords: Motivation; Shared service center; Accounts payable; Commitment; Repetitive tasks.